Find the unknown side length, x. Write your answer in simplest radical form. A. 4 B. Square root of 65 C. 11 D. 5 square root 13
Find the unknown side length, x. Write your answer in - 1

Answers

Answer 1
Answer:

Answer:

x=√(65)

B is the correct option.

Step-by-step explanation:

We'll use Pythagorean theorem to find the value of x.

In right angle ABC, applying Pythagorean theorem, we get

BC=√(5^2-3^2)\n\nBC=√(16)\n\nBC=4

Now, in right angle triangle CBD,

x=√(7^2+4^2)\n\nx=√(49+16)\n\nx=√(65)

B is the correct option.

Answer 2
Answer:

Answer:

B. square root of 64

Step-by-step explanation:


Related Questions

How do you solve 5(x+4) = 3x + 23
5. Joan asked 30 randomly selected adult restaurant customers about their choice of beverages. 18 customers said coffee is their favorite beverage. If the restaurant serves 200 adult customers per day, estimate the number who will choose coffee to drink.A. 100 B. 110 C. 120 D. 130 6. You are surveying students to find out their opinion of the quality of food served in the school cafeteria. You decide to poll only those students who buy hot lunch on a particular day. Is your sample random? Please explain
*HELP PLEASE WILL THANK AND AWARD BRAINLIEST ANSWER*Given figure ABCD ~ figure KLMN, what is the value of y?   A.1.2 cm  B.3.6 cm  C.4 cm D.12 cm
Write the ratio in simplest form 50:35
How to identify the bases and faces of each figure then name the figure

21 trucks, each with a 2.5-ton payload, are needed to unload a freight train. How many trucks, each with a 3.5-ton payload, would be needed to do the same job? What is the constant of variation?

Answers

tons needed to unload a freight train= 21×2.5 =52.5
number of 3.5-ton payload trucks needed to unload a freight train=52.5÷3.5 = 15

15 Trucks , Each With A 3.5-Ton Payloaf , Would be Needed To Do The Same Job. 

Joan walked 23 1/4 miles in a week. Her sister walked 69 3/4 miles during the same week. How many times farther did Joan’s sister walk than Joan?

Answers

joans sister walked 3 times farther.

23 1/4 * 3 = 69 3/4

joans sister walked 3 times farther.

How do you solve a quadratic equation

Answers

- \beta +- √( \beta )  {2} -4ac (all divided by)/2a
You should already know how to factor quadratics. (If not, review Factoring Quadratics.) The new thing here is that the quadratic is part of an equation, and you're told to solve for the values of x that make the equation true. Here's how it works: Solve (x – 3)(x – 4) = 0. Okay, this one is already factored for me. But how do I solve this?Think: If I multiply two things together and the result is zero, what can I say about those two things? I can say that at least one of them must also be zero. That is, the only way to multiply and get zero is to multiply by zero. (This is sometimes called "The Zero Factor Property" or "Rule" or "Principle".) Warning: You cannot make this statement about any other number! You can only make the conclusion about the factors ("one of them must equal zero") if the product itself equals zero. If the above product of factors had been equal to, say, 4, then we would still have no idea what was the value of either of the factors; we would not have been able (we would not have been mathematically "justified") in makingany claim about the values of the factors. Because you can only make the conclusion ("one of the factors must have equaled zero") if the product equals zero, you must always have the equation in the form "(quadratic) equals (zero)" before you can attempt to solve it.  The Zero Factor Principle tells me that at least one of the factors must be equal to zero. Since at least one of the factors must be zero, I'll set them eachequal to zero:x – 3 = 0   or   x – 4 = 0This gives me simple linear equations, and they're easy to solve:x = 3  or  x = 4And this is the solution they're looking for:  x = 3, 4Note that "x = 3, 4" means the same thing as "x = 3  or  x = 4"; the only difference is the formatting. The "x = 3, 4" format is more-typically used.One important issue should be mentioned at this point: Just as with linear equations, the solutions to quadratic equations may be verified by plugging them back into the original equation, and making sure that they work, that they result in a true statement. For the above example, we would do the following: Checking x = 3 in (x – 3)(x – 4) = 0:([3] – 3)([3] – 4) ?=? 0 
     (3 – 3)(3 – 4) ?=? 0
 
               (0)(–1) ?=? 0
 
                       0   =   0
Checking x = 4 in (x – 3)(x – 4) = 0:([4] – 3)([4] – 4) ?=? 0 
     (4 – 3)(4 – 4) ?=? 0
 
                 (1)(0) ?=? 0
 
                       0   =   0
So both solutions "check" and are thus verified as being correct.Solve x2 + 5x + 6 = 0.This equation is already in the form "(quadratic) equals (zero)" but, unlike the previous example, this isn't yet factored. The quadratic must first be factored, because it is only when you MULTIPLY and get zero that you can say anything about the factors and solutions. You can't conclude anything about the individual terms of the unfactored quadratic (like the 5x or the 6), because you can add lots of stuff that totals zero.So the first thing I have to do is factor:x2 + 5x + 6 = (x + 2)(x + 3)Set this equal to zero:(x + 2)(x + 3) = 0Solve each factor: Copyright © Elizabeth Stapel 2002-2011 All Rights Reservedx + 2 = 0  or  x + 3 = 0 
x = –2  or  x = – 3
The solution to x2 + 5x + 6 = 0 is x = –3, –2Checking x = –3 and x = –2 in x2 + 5x + 6 = 0:[–3]2 + 5[–3] + 6 ?=? 0 
           9 – 15 + 6 ?=? 0
 
           9 + 6 – 15 ?=? 0
 
               15 – 15 ?=? 0
 
                        0   =   0
[–2]2 + 5[–2] + 6 ?=? 0 
           4 – 10 + 6 ?=? 0
 
           4 + 6 – 10 ?=? 0
 
               10 – 10 ?=? 0
 
                        0   =   0
So both solutions "check".Solve x2 – 3 = 2x.This equation is not in "(quadratic) equals (zero)" form, so I can't try to solve it yet. The first thing I need to do is get all the terms over on one side, with zero on the other side. Only then can I factor and solve:x2 – 3 = 2x 
x2 – 2x – 3 = 0 
(x – 3)(x + 1) = 0 
x – 3 = 0  or  x + 1 = 0 
x = 3  or  x = –1
Then the solution to x2 – 3 = 2x is x = –1, 3Solve (x + 2)(x + 3) = 12.It is very common for students to see this type of problem, and say:"Cool! It's already factored! So I'll set the factors equal to 12 and 
solve to get x = 10 and x = 9. That was easy!"Yeah, it was easy; it was also (warning!) wrong. Besides the fact that (10 + 2)(9 + 3) does not equal 12, you should never forget that you must have "(quadratic) equals (zero)" before you can solve.So, tempting though it may be, I cannot set each of the factors above equal to the other side of the equation and "solve". Instead, I first have to multiply out and simplify the left-hand side, then subtract the 12 over to the left-hand side, and re-factor. Only then can I solve.(x + 2)(x + 3) = 12 
x2 + 5x + 6 = 12 
x2 + 5x – 6 = 0 
(x + 6)(x – 1) = 0 
x + 6 = 0  or   x – 1 = 0 
x = –6  or   x = 1
Then the solution to (x + 2)(x + 3) = 12 is x = –6, 1

Which function represents g(x), a reflection of f(x) = (3)x across the y-axis?g(x) = 2(3)x
g(x) = −(3)x
g(x) = (3)−x
g(x) = 2(3)−

Answers

Answer: g(x)=(3)^(-x)

Step-by-step explanation:

We know that if a figure is reflected across y axis then its y coordinate remains same but the x coordinate changes its polarity.

i.e. the function f(x) will become f(-x) .

Now, the given function :f(x)=(3)^x

Then , after reflection across y axis the new function will become:

g(x)=f(-x)=(3)^(-x)

By how many cm is 1/10 m longer than 1/100 m

Answers

a= 1/10 m = 10 cm
b= 1/100 m = 1 cm
a - b = 9 cm

I am having questions about how to solve problems like this. Anyone able to help?

Answers

For your first answer z=60 because 360/6 
For your second answer y=128 you must add the two sides then subtract the answer from 360 to get 128
For your third answer for x=120 and 2x=100